Estimation of the Two Parameters for Generalized Rayleigh Distribution Function Using Simulation Technique - AL- Naqeeb, A. A .; Hamed, A. M . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, suggested formula as well a conventional method for estimating the twoparameters (shape and scale) of the Generalized Rayleigh Distribution was proposed. For different sample sizes (small, medium, and large) and assumed several contrasts for the two parameters a percentile estimator was been used. Mean Square Error was implemented as an indicator of performance and comparisons of the performance have been carried out through data analysis and computer simulation between the suggested formulas versus the studied formula according to the applied indicator. It was observed from the results that the suggested method which was performed for the first time (as far as we know), had highly advantage than the studied method, since the whole suggested outcomes of statistics in the suggested method are registered.